Imperatives of Strengthening Governance in the World Bank’s Engagement in Iraq, 2014–2018 - A. I. Solomatin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Arab Awakening became a watershed event for the states of the Middle East and North Africa (MENA) and changing the political landscape of the entire region. The crisis in the Arab world provoked an unprecedented strengthening of the Salafi jihadist groups, in particular, the notorious Islamic State in Iraq and al-Sham (ISIS). In 2014 ISIS took over large swathes of territory in war-torn Syria and Iraq, which had gone through a complex and extremely risky process of nation-building after overthrow of Saddam Hussein’s regime. In June of 2014 ISIS proclaimed a ‘caliphate’ on the territories under its control. In contrast with the Assad government in Syria, the Iraqi authorities received various kinds of support in fighting Islamic State from Western countries and the organizations with their predominant influence, including the World Bank Group. Since then stabilization and reconstruction of liberated areas in Iraq have become a priority for these organizations in their work in the MENA region. This paper examines the determinants of the World Bank’s engagement in Iraq after the establishment of a ‘сaliphate’ and the motives behind choosing particular modalities, channels, instruments and priority sectors in its policies towards Iraq during this period. The paper consists of three sections. The first section sheds light on the World Bank’s priorities in Iraq in the context of evolution of its regional strategy after the Arab Awakening. The second section examines individual World Bank projects launched after June of 2014. The third section focuses on the role of the World Bank in preparing needs assessments and policy papers for the Iraqi government after declaration of victory over ISIS. The conclusion is drawn that the Bank’s activities in Iraq after 2014 represent a remarkable example of securitization of development agenda of this pivotal multilateral institution. The Bank was clearly guided not by economic but by political and strategic motives while developing its strategy of engagement in Iraq after the ISIS offensive. The World Bank projects in Iraq during 2014–2018 period were primarily aimed at strengthening governance and restoring the citizens’ trust in the state institutions in the most vulnerable to radicalization regions of the country.